Near infrared reflective pigments based on Bi3YO6 for heat insulation. Issue 15 (15th October 2020) - Chen, Jinqing; Xie, Wenqi; Guo, Xiangguang; Huang, Bin; Xiao, Yu; Sun, Xiaoqi
Abstract: In this paper, a series of high performance near-infrared reflective pigments based on Bi3 YO6 doped with Fe2 O3 and Tb4 O7 were prepared by high-temperature calcination method. The pigments were characterized by some analytic techniques, such as XRD, Particle size analyzer, SEM, EDS, UV–vis–NIR spectrophotometer, CIE L*a*b* (1976) color space and infrared thermal imaging. Experimental results showed that the Fe2 O3 doping in Bi3 YO6 could change the color from bright yellow to ochre red. The substitution of Tb (IV)-doped pigments changed the color to dark orange. The doping of Fe (III) and Tb (IV) contributed to enriching the color diversities of pigments. Among the synthesized pigments, Bi3-x Fex YO6 and Bi3 Y1-x Tbx O6+δ displayed a disordered defective fluorite-type structure. The effect of doping Fe (III) and Tb (IV) reduced the near-infrared reflectance of the pigment. Excepting for Bi3-x Fex YO6 (x = 0.8), the near infrared reflectance of some other pigments were higher than the China National standard (CNs). Chemical resistance tests showed that the pigments had excellent acid and alkali resistance. Finally, the application practical of traditional iron oxide yellow pigment and three prepared pigments, i.e., Bi3 YO6, Bi3-x Fex YO6 (x = 0.4) and Bi3 Y1-x Tbx O6+δ (x = 0.05) were studied and compared by infrared thermal imaging. The test results showed that Bi3 YO6 still had a strong near-infrared reflection effect after being painted. Compared with traditional iron yellow pigment, Bi3 YO6 could reduce the surface temperature of galvanized sheet by 20 °C under the illumination of infrared light. The series of Fe (III) and Tb (IV) doped pigments prepared in this paper have revealed some promising application values.